2012 Vierna et al. North West Atlantic distribution of Ensis directus ... - Joaquin Vierna (The Archive for Marine Species and Habitats Data (DASSH), 2024)
We report current genetic variation of populations of the razor shell Ensis directus (Conrad 1843) (Mollusca: Bivalvia: Pharidae) in native (North American) and introduced (European) ranges using nuclear and mitochondrial sequence-based markers. This dataset is a subset and relates only to ad-hoc sightings mentioned in the report of this species occurring in The Wash. ... : Part of MSFD NNS baseline data collation project (Jan 2016). Subset of a dataset as we were only pulling out records for a selection of INNS. Contains records for Ensis directus. See Vierna, J., Jensen, K.T., González-Tizón, A.M. et al. Population genetic analysis of Ensis directus unveils high genetic variation in the introduced range and reveals a new species from the NW Atlantic. Mar Biol 159, 2209–2227 (2012). DOI 10.1007/s00227-012-2006-6 for original source. ...